The university under pressure - Berman, Elizabeth Popp, 1975-; Paradeise, Catherine (Research in the sociology of organizations ;, 2016)
Universities are under pressure. Their resource environment is evolving, demands for accountability have increased and demographic shifts are changing higher educational needs. This volume provides a cross-national picture of how the university as an organization is reacting to, adapting to, and threatened by a period of intense pressure.